2015
DOI: 10.1097/ede.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Residential Exposure to Estrogen Disrupting Hazardous Air Pollutants and Breast Cancer Risk

Abstract: Background Some studies show increased breast cancer risk from exposure to xenoestrogens, but few have explored exposures via ambient air, which could impact large populations. Objectives This study explored the association between breast cancer risk and residential exposures to ambient estrogen disruptors among participants in a large cohort study, the California Teachers Study. Methods Participants consisted of 112,379 women free of breast cancer and living at a California address in 1995/1996. Eleven ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 33 publications
0
51
3
Order By: Relevance
“…Multiple studies (2, 3), but not all (4, 7), found that exposure to traffic-related air pollutants, particularly NO 2 , increased breast cancer risk. A potential explanation for differences among studies could be differing proportions of ER/PR subtypes, if as our data suggest, NO 2 is only associated with ER+/PR+ breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies (2, 3), but not all (4, 7), found that exposure to traffic-related air pollutants, particularly NO 2 , increased breast cancer risk. A potential explanation for differences among studies could be differing proportions of ER/PR subtypes, if as our data suggest, NO 2 is only associated with ER+/PR+ breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, a 2010 case-control study reported a 1.3-fold increased risk of breast cancer (95% CI of OR: 1.0–1.7) for every 5 ppb increase in NO 2 assessed via a land-use regression spatial model (3). The California Teachers Study recently reported an increased risk for ER−/PR− breast cancer associated with endocrine disruptors present in ambient air, namely cadmium compounds and inorganic arsenic (4). However, to date, relatively few studies have investigated the link between air pollution and breast cancer subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…In analyses stratified by tumor subtype, some of the air pollutants were associated with estrogen-receptor-positive and progesterone-receptor-positive (ER+ and PR+) tumors; other constituents have been associated with receptor-negative subtypes only. Positive associations have been identified between ER+/PR+ tumors and ambient levels of NO 2 , acrylamide, benzidine, carbon tetrachloride, ethylidene dichloride, and vinyl chloride, and between ER-negative/PR-negative (ER-/PR-) subtypes and ambient levels of benzene, cadmium, and inorganic arsenic [19, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the role of diet, particularly for non-smoking subjects (European Food Safety Authority, 2012), and outdoor pollution due to industrial emissions, fossil fuel combustion, solid waste incineration and traffic exhausts is still not well defined, since little epidemiologic evidence is available (Hogervorst et al, 2007;Liu et al, 2015). In this study, we aimed to assess Cd exposure in the general population of a Northern Italian community, and in addition we sought to identify the independent role of three sources of Cd exposure: smoking habits, diet and outdoor air pollution.…”
Section: Introductionmentioning
confidence: 99%